Experience of Daratumumab in Six Patients With Multiple Myeloma and Kidney Failure. (September 2021) - Turgutkaya, Atakan; Bolaman, Ali Zahit; Yavaşoğlu, İrfan
Purpose: Daratumumab, a monoclonal anti-CD38 antibody, has been administered for relapsed refractory multiple myeloma (RRMM). The Pollux and Castor trials proved its efficacy, yet excluded patients with advanced-stage renal disease. Therefore, available experience in these patients is limited. Here, we aimed to emphasize the safety of daratumumab in 6 patients with kidney disease. Methods: Six patients with RRMM diagnoses and renal impairment were included. Their mean ± standard deviation age was 63.6 ± 8.38 years. Three, two, and one patient(s) had immunoglobulin (Ig) G kappa, lambda light chain, and IgA lambda MM, respectively. All patients received 4 to 6 lines of anti-MM therapy before daratumumab treatment. Five had chronic kidney disease and 1 was admitted to the hospital with acute kidney injury due to myeloma relapse. Daratumumab was administered to all patients with close follow-up. Results: Following treatment with daratumumab, kidney function was improved in 1 patient. In 1 patient, the glomerular filtration rate was slightly decreased and hemodialysis was initiated. In 2 patients already receiving hemodialysis, their dependency on hemodialysis continued. No adverse reactions were recorded. One patient achieved complete remission and 4 patients achieved very good partial remission. Conclusion: Daratumumab can be administered safely, with improvements in kidney function possible in some patients. Studies involving larger patient groups are required to obtain more accurate data.